2015
DOI: 10.1038/nm.3778
|View full text |Cite|
|
Sign up to set email alerts
|

Myeloid-derived growth factor (C19orf10) mediates cardiac repair following myocardial infarction

Abstract: Paracrine-acting proteins are emerging as a central mechanism by which bone marrow cell-based therapies improve tissue repair and heart function after myocardial infarction (MI). We carried out a bioinformatic secretome analysis in bone marrow cells from patients with acute MI to identify novel secreted proteins with therapeutic potential. Functional screens revealed a secreted protein encoded by an open reading frame on chromosome 19 (C19orf10) that promotes cardiac myocyte survival and angiogenesis. We show … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

10
211
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 181 publications
(222 citation statements)
references
References 55 publications
10
211
1
Order By: Relevance
“…41 Successful acute IR injury was confirmed not only by visual inspection of left ventricle (LV) color alteration but also by ST-segment-characterized electrocardiogram.…”
Section: Mouse Model Of Myocardial Irmentioning
confidence: 97%
“…41 Successful acute IR injury was confirmed not only by visual inspection of left ventricle (LV) color alteration but also by ST-segment-characterized electrocardiogram.…”
Section: Mouse Model Of Myocardial Irmentioning
confidence: 97%
“…105,106 Similar to other striated muscles, the injured cell milieu generated by the damage dictates the tropism of resident progenitor and stem cells to the injury site, mediating a certain degree of self-recovery, [103][104][105][106][107] but since the adult cardiomyocytes are known to be in mitotic arrest, this limits the repair mechanism. 108,109 Thus, considering the low regeneration potential of the endogenous mechanisms attempts to stimulate regeneration by using exogenous stem cells seem plausible.…”
Section: Myocardial Infarctionmentioning
confidence: 99%
“…First, CDC-modulated macrophages may secrete factors with antiapoptotic actions. A recent study identified infarct monocytes and macrophages as an important source of myeloid-derived growth factor (MYDGF), a secreted protein that promotes cardiomyocyte survival (13 The mammalian heart contains a population of resident macrophages that expands in response to myocardial infarction through the recruitment of monocytes. Infarct macrophages exhibit high phenotypic diversity and respond to microenvironmental cues by altering their functional properties and secretory profile.…”
Section: Macrophages Regulate Cardiomyocyte Survival In Ischemic Myocmentioning
confidence: 99%